Predominantly Diurnal, Bimodal-Crepuscular Activity Patterns of Sun Bears (Helarctos malayanus) in Bukit Tiga Puluh National Park, Sumatera, Indonesia - Subagyo, Agus; Sinaga, Joshua; Dwi Kartika, Winda; Hisan, Muhammad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The sun bear (Helarctos malayanus) is a vulnerable species listed on the IUCN Red List, whose behavioral ecology is critically shaped by habitat conditions. Increasing deforestation pressure in and around Bukit Tiga Puluh National Park (BTNP), Sumatra, highlights the urgency of understanding the spatiotemporal activity patterns of this species to support evidence-based conservation. This study analyzes the diel activity patterns of sun bears using secondary (bycatch) camera trap data collected by PKHS from 103 stations in BTNP between 2017 and 2022. From a total of 35,619 trap-days, 647 independent video detections were obtained. Kernel Density Estimation (KDE) analysis revealed a predominantly diurnal (62.44%) and strongly bimodal activity pattern. Activity peaks were recorded in the morning (06:00–09:00 WIB) and late afternoon (16:00–19:00 WIB), with a marked reduction during midday (11:00–14:00 WIB). This bimodal pattern indicates crepuscular characteristics, likely reflecting thermoregulatory adaptation and foraging strategies. The persistence of a strong diurnal signal suggests that BTNP continues to function as a relatively potential refuge from anthropogenic disturbance, although this inference is indirect, as human disturbance intensity was not measured directly. These findings provide a temporal basis for designing more effective anti-poaching patrol schedules and human–wildlife conflict mitigation strategies.